Human trafficking interdisciplinary perspectives - Burke, Mary C. (Mary Cecilia) (Criminology and justice studies, 2013)
The practice of one human being exploiting another in slavery-like conditions is not new. Today, it is called human trafficking. Social, political, and economic forces over the past 60 years have changed how and why this human rights abuse occurs. In order to solve this or any social problem, it is important that it is fully understood. With a range of contributing subject experts from different disciplines and professions, this text comprehensively explains human trafficking as it exists and is being addressed in the twenty-first century. Human Trafficking is essential reading for professionals working in many fields, including law enforcement, human services, and health care, and for concerned citizens interested in human rights and how to make a difference in their communities. This book is also intended for use in undergraduate and graduate interdisciplinary courses in human trafficking.